Does the level of myocardial injury differ in primary angioplasty patients loaded first with clopidogrel and the ones with ticagrelor? - Nil Ozyuncu; Hüseyin Göksülük; Turkan Seda Tan; Kerim Esenboga; Yusuf Atmaca; Çetin Erol (Anatolian Journal of Cardiology)
Objective: In daily clinical practice, we encounter ST segment elevation myocardial infarction (STEMI) patients loaded with clopidogrel upon admission to primary angioplasty. These patients are loaded with ticagrelor, if there is no contraindication. This study aimed to compare the level of injury between STEMI patients who were first loaded with clopidogrel and the ones first loaded with ticagrelor. Although patients were switched from clopidogrel to ticagrelor at the first hour of angioplasty, antiplatelet action may still be lower than the others. Methods: This study included STEMI patients with angina onset of ≤3 h and who had primary angioplasty to proximal segment of one coronary artery. All patients had total thrombotic occlusion at the proximal segment. Δtroponin level (6th-hour troponin–admission troponin) was calculated to compare the level of myocardial injury. Results: A total of 105 patients were included; 52 were loaded with ticagrelor and 53 with clopidogrel first and switched to ticagrelor. Baseline characteristics were similar in the two groups, except from type B2 lesions being more common in the ticagrelor-loaded group. Δtroponin levels were significantly higher in the clopidogrel-loaded group compared with the ticagrelor-loaded group (p=0.013). Major bleeding and in-hospital MACE rates were similar in both groups. Conclusion: In STEMI patients, the degree of troponin rise was more prominent in clopidogrel-loaded patients, despite the switch to ticagrelor in the first hour of intervention. Clopidogrel is slow and modest, and variable platelet inhibition may continue to be a negative factor for protection from myocardial injury, even after switching to ticagrelor.